2006
DOI: 10.1038/sj.onc.1209800
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B-cell leukemia transcription factor 1 is a major target of promyelocytic leukemia zinc-finger-mediated melanoma cell growth suppression

Abstract: Promyelocytic leukemia zinc-finger (PLZF) is a transcriptional repressor and tumor suppressor. PLZF is expressed in melanocytes but not in melanoma cells, and recovery of PLZF expression markedly suppresses melanoma cell growth. Several target genes regulated by PLZF have been identified, but the precise function of PLZF remains uncertain. Here, we searched for candidate target genes of PLZF by DNA microarray analysis. Pre-B-cell leukemia transcription factor 1 (Pbx1) was one of the prominently suppressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
(32 reference statements)
2
39
0
Order By: Relevance
“…Furthermore, NKT cells are not dependent on PLZF to undergo proliferation, as has been shown in PLZF-deficient mice (16,17). Indeed, PLZF has been reported to inhibit cell cycle progression (45,46) and to cause cell quiescence (47) and suppression of cell growth (48). Therefore, it is possible that the NKT cell proliferative burst is actually dependent on the rapid downregulation of PLZF that we reported (16).…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, NKT cells are not dependent on PLZF to undergo proliferation, as has been shown in PLZF-deficient mice (16,17). Indeed, PLZF has been reported to inhibit cell cycle progression (45,46) and to cause cell quiescence (47) and suppression of cell growth (48). Therefore, it is possible that the NKT cell proliferative burst is actually dependent on the rapid downregulation of PLZF that we reported (16).…”
Section: Discussionmentioning
confidence: 63%
“…Besides hematopoietic malignancy, PBX1 is also highly expressed in solid tumors including melanoma, prostate, ovarian, and breast cancers (23)(24)(25). In ovarian cancer, PBX1 has been identified as an effector in the NOTCH3 signaling pathway, which is known to maintain stemness and promote platinum drug resistance in ovarian cancer cells (10,26).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that enforced expression of Pbx1 alone was not sufficient to restore the decreased colony-forming capacity of Evi-1 À/À P-Sp cells (data not shown). These Pbx1 has also been implicated in the development of several tumors including hematological malignancies (Kamps et al, 1990(Kamps et al, , 1991Nourse et al, 1990;Qiu et al, Shiraishi et al, 2007;Park et al, 2008). It is required for the execution of some Hox-dependent block of differentiation, and/or transformation (Krosl et al, 1998;Knoepfler et al, 2001;Yaron et al, 2001), and mutations of HoxA9 that prevent interaction with Pbx proteins abrogate its oncogenic properties (Schnabel et al, 2000).…”
Section: Evi-1 Activates Pbx1 Transcription M Shimabe Et Almentioning
confidence: 99%